THE IMPACT OF DIGITAL HEALTH PLATFORMS ON PROMOTING HEALTHY LIFESTYLE HABITS AMONG 10–11 GRADE HIGH SCHOOL STUDENTS IN UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2025)
In recent years, digital technologies have become a powerful tool for improving the health and lifestyle of young people. This research focuses on how digital health platforms—such as mobile applications, websites, and social media campaigns—help promote healthy lifestyle habits among 10–11 grade high school students in Uzbekistan. The study explores the influence of multiplatform digital tools on students’ physical activity, nutrition, and mental well-being. It also analyzes how these technologies can support the goals of national health programs and school-based health education. The results show that digital platforms can play a significant role in motivating teenagers to be more active, eat healthier, and manage stress effectively when used systematically within schools and families.